Analisis Framing Pemberitaan Pasca Bencana Banjir Sumatra dalam Media Kompas.Com: Analisis Framing Model Robert M. Entman pada Artikel Media Kompas.Com - Rafii Fadilah Rahmman; Ana Fitriana Poerana; Nurkinan Nurkinan (Comit: Communication, Information and Technology Journal, 2026)
This research is motivated by the high intensity of hydrometeorological disasters in Indonesia, specifically the devastating flash floods and landslides that struck three provinces in Sumatra in November 2025. During this crisis phase, mass media plays a crucial role in constructing social reality and influencing public perception regarding the post-disaster management process. This study aims to determine and analyze how the digital news portal Kompas.com framed information related to the crisis recovery progress through an article titled "Dua Bulan Pascabencana Sumatera, Bagaimana Progres Penanganannya?". The method used in this research is a descriptive qualitative method based on the constructivism paradigm. Primary data collection was conducted through news text documentation, supported by secondary data from a literature review. The obtained data were then analyzed using Robert M. Entman's framing analysis model, which examines news texts based on four structural devices: define problems, diagnose causes, make moral judgement, and treatment recommendation. The analysis results show that Kompas.com critically defined the post-disaster reality in Sumatra as a slow, difficult, and unequal recovery process, particularly in the Aceh region. The media diagnosed that the slow recovery was caused by topographical damage, the absence of dams in the upstream areas, and the dilemma of emergency bridges bearing the overload of logistics vehicles. Through its moral judgement, the media performed a watchdog function to demand government accountability and transparency. As a resolution, Kompas.com emphasized the importance of long-term interventions based on structural mitigation, such as the provision of an IDR 74 trillion budget for dam projects. Overall, this news reporting represents the practice of disaster journalism that encourages the creation of human security and future community resilience.